2020
DOI: 10.14295/bds.2021.v24i1.2304
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability of Bulk Fill Composite Resins Submitted to Coffee Staining

Abstract: Objective: The aim of this in vitro study was to evaluate the color stability of different bulk fill composite resins after extrinsic staining with coffee. Material and methods: Forty-eight disk-shaped specimens (6 mm diameter x 2 mm thick) of each composite resin were prepared for color change test. The composite resins were divided into 4 groups (n=12): one conventional composite resin (Filtek Z250) and three bulk-fill composite resins (Filtek Bulk Fill, Aura Bulk Fill, and Opus Bulk Fill). The samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
8
0
2
Order By: Relevance
“…Papers included in this review investigated several staining liquids. Coffee was used in most studies ( n = 16), 13,14,28,50–52,54–60,62–64 followed by coke ( n = 6), 14,54,59,61,64,65 red wine ( n = 5), 13,14,54,59,64 tea ( n = 4), 51,54,55,58 orange juice ( n = 3), 51,58,61 other juices ( n = 3), 51,55,62 and energy drinks ( n = 1) 65…”
Section: Resultsmentioning
confidence: 99%
“…Papers included in this review investigated several staining liquids. Coffee was used in most studies ( n = 16), 13,14,28,50–52,54–60,62–64 followed by coke ( n = 6), 14,54,59,61,64,65 red wine ( n = 5), 13,14,54,59,64 tea ( n = 4), 51,54,55,58 orange juice ( n = 3), 51,58,61 other juices ( n = 3), 51,55,62 and energy drinks ( n = 1) 65…”
Section: Resultsmentioning
confidence: 99%
“…When Sişmanolu S and Sengez G did a study to examine the effects of acidified drinks on the staining of bulk-fill composites materials of various viscosities, they discovered that all of the bulk-fill composites materials tested showed staining considerably over a clinically appropriate threshold. A study was carried out by De Arruda BM et al [23] to examine how long different BF composites would retain their colour after being externally darkened with coffee. Coffee-induced extrinsic staining was a threat to all of the composite materials evaluated, with BF composite showing the least degree of colour change.…”
Section: Discussionmentioning
confidence: 99%
“…Şişmanoğlu S and Sengez G [22] found that all bulk-fill composites materials analyzed, showed staining well above a clinically reasonable threshold when they conducted research to look into the implications of acidified beverages on the staining of bulk-fill composites materials of various viscosities. De Arruda BM et al [23] conducted a study to scrutinize the durability of the colour of various BF composites following external darkening with coffee. All of the composite materials tested were vulnerable to extrinsic staining induced by coffee, with BF composite exhibiting the least amount of colour change.…”
Section: Effect Of Different Beverages and Drinks Over The Changes In...mentioning
confidence: 99%
“…These findings could be due to the fact that the Opus Bulk Fill resin composite resin works with a new advanced polymerization system (APS) technology that reduces the amount of camphorquinone by incorporating other types of initiators and co-initiators that are secrets of the brand and do not require activation with light in the violet spectrum, amplifying the polymerization capacity and increasing the conversion degree and depth of LED curing, which would improve the mechanical and surface properties [ 49 ]. It should be noted that the matrix composition is not well-described by the manufacturer [ 50 ]. Therefore, according to what was obtained in the present study, we can assume that this APS technology present in Opus Bulk Fill was improved by the OIL control, allowing it to function properly as described by the manufacturer, resulting in better surface microhardness.…”
Section: Discussionmentioning
confidence: 99%